(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Cyathula prostrata (L) Blume commonly known as Pasture weed, pig weed, and prickly chaff-flower, and is a native to tropical and subtropical regions of Asia and Africa. It is a herbaceous plant and grows up to a height of 1-2 meters. The plant belongs to the family of Amaranthaceae. The entire plant including the roots, stems, leaves and flowers of the plant are used in traditional medicine for treatment of various dysentery, Diarrhea, scabies, rheumatism, inflammation and many others. The extract of the plant consists of various phytoconstituents such as flavonoids, alkaloids, glycosides, saponins and phenolic acids. Urolithiasis or kidney stones formation is prevalent and painful condition affecting millions worldwide. This study aimed to investigate the antiurolithiatic potential of Cyathula prostrata and to formulate a pharmaceutical preparation for its effective utilization. Phytochemical analysis revealed presence of bioactive compounds including flavonoids, alkaloids, saponins, phenolic acids and glycosides. The study shows antiurolithiatic potential of Cyathula prostrata and offers a formulation for its prevention and treatment. To enhance its therapeutic usability, a herbal syrup formulation was developed using the decoction of Cyathula prostrata combined with a simple syrup base. The syrup was evaluated for physical characteristics such as color, taste, viscosity, and stability, making it a convenient and palatable dosage form for potential future use. The aqueous extract of Cyathula prostrata has shown promising effects in reducing the size of calcium oxalate crystals, which are the most common type of kidney stones. Thus, Cyathula prostrata holds potential as a natural remedy for managing nephrolithiasis.